The Effect of Decreased Intensity of Physical Activity in Former Athletes on the Incidence of Depression: Literature Review: English - Refianisa, Salwa; Klafinofa, Hanifa Rahmatya (Asosiasi Program Studi Olahraga PGRI Indonesia (APOPI), 2023)
In general, physical activity is needed for athletes. Doing physical activity will also have a good impact on the body so this indicates that physical activity can be a measure of individual health. However, after the end of an athlete's career, there is a decrease in the intensity of physical activity which causes a negative impact in the form of depression on former athletes. This article was prepared using the systematic literature review method which aims to provide information about the effect of decreasing the intensity of physical activity in former athletes on the incidence of depression. The articles used were obtained from the Garba Digital Reference (GARUDA) database and PubMed. There were 7 relevant journal articles based on the selection results by adjusting the inclusion and exclusion criteria. The results obtained in this article are evidence of the effect of reducing the intensity of physical exercise has a negative impact on former athletes. Many psychological problems arise, such as frustration and depression. Although there are many environmental factors that affect psychological disorders, but with the routine physical exercise that is usually done by a former athlete has more impact on his psychological condition.